UTM INTERNATIONAL STUDENTS’ PERSPECTIVE ON INTERCULTURAL ADAPTATION AND COMPETENCE (Jurnal Kemanusiaan, 2017)
ABSTRACTMost of the previous studies attempted to investigate intercultural communication competence (ICC) from the students’ perspectives. Other studies were done on adaptation and adjustment reporting the experiences of expatriates in this regard. However, the current study is one of the few studies investigating adaptation on the light of intercultural communication. A detailed questionnaire with different sections is used in the current study to achieve its aims and objectives. The current study is systematic in terms that it uses the theory of cross-cultural adaptation as the theoretical framework to investigate the issues in hand. Three dimensions of the cross-cultural communication model are highlighted and investigated in this study namely: social communication, personal communications and predispositions. Using manual analysis, the study explores intercultural competence and adaptation experiences of international students.